Too much too soon?: Perceived appropriateness of sexting across stages of relationship development and attachment tendencies among emerging adults. (December 2022) - Guest, Chelsea; Denes, Amanda
Abstract: One communication pattern afforded by smartphones is sexting. When considering sexting as an intimate form of sexual-self disclosure, concepts like perceived appropriateness must be considered. The current project assessed how the frequency and perceived appropriateness of sexting varied across relationship stages and across different attachment tendencies among emerging adults. Results from a cross-sectional survey ( N  = 133) indicate linear relationships, such that sexting tended to increase in frequency and perceived appropriateness alongside the stages of relationship development. Further, relationship stage did not interact with attachment tendencies, but attachment avoidance demonstrated a negative relationship with sexting frequency. Theoretical and practical implications are discussed further. Highlights: This study explores the frequency and perceptions of sexting across stages of relationships and across different attachment dimensions among emerging adults. Sending and receiving sexts is more frequent in the later stages of relationships. Attachment avoidance demonstrated a negative relationship with sexting frequency. Attachment anxiety was not related to the frequency of sexts sent or received. Sexting is perceived to be more appropriate in the later stages of relationships.